Providing health care in rural and remote areas: lessons from the international space station - Papali, Alfred (Bulletin of the World Health Organization, 2016)
Circumnavigating the globe every 90 minutes, 400 km above the Earth's surface and at a speed of 27 600 km per hour, the international space station typically does not evoke thoughts of rural Haiti. An isolated extraterrestrial outpost of humanity, it represents a marvel of human engineering and ingenuity. It is this very isolation, ironically, that gives it something in common with rural areas in low- and middle-income countries here on Earth. When thinking about the vexing barriers to improving emergency care, you can look to the sky to find solutions -- the space station provides three examples of what might work. Task-shifting, point-of-care ultrasound and telemedicine services, if scaled up as part of an organized, collaborative approach among diverse interests, are three methods that might improve access to -- and quality of -- care in rural and remote areas.